Ten-week lifestyle changing program reduces several indicators for metabolic syndrome in overweight adults - Mecca, Marita S. [UNESP]; Moreto, Fernando [UNESP]; Burini, Franz H. P. [UNESP]; Dalanesi, Reinaldo C. [UNESP]; Mclellan, Katia Cristina Portero [UNESP]; Burini, Roberto Carlos [UNESP] (Biomed Central Ltd., 2012)
We aim to investigate the effectiveness of a 10-week lifestyle intervention focusing on physical activity and high fiber intake for reducing indicators for metabolic syndrome in overweight-obese individuals. A prospective study of 50 overweight (OW) adults (22 in the general educational group - G1; 28 in the high fiber nutrition group - G2) was performed. Both groups were offered dietary counseling and supervised exercise. Clinical, anthropometric, dietary and plasma biochemical tests were performed at baseline - time 0 (T0) and after 10 weeks - time 1 (T1). Both groups improved their dietary quality, but only G2 presented higher intake of fruit and vegetables (servings/day), higher plasma beta-carotene levels and a 24% reduction of MetS incidence. Additionally G2 showed greater reductions in body fat (4%), and waist circumference (7%), obesity class III (2%) and obesity class II (14%) rate. Lifestyle intervention, including a high dietary fiber intake, improved healthy eating index and decreased body fat composition and plasma lipid concentrations leading to MetS incidence reduction.